Yule's lambdagram revisited and reclaimed - Terence C. Mills (Economics & Finance Research, 2013)
In this article, the lambdagram, proposed by Yule in his last time series paper published in 1945, is revisited using modern theoretical and computational developments unavailable to him. Although it is not particularly good at identifying stationary processes, the lambdagram is found to be much more useful for distinguishing between trend and difference stationary processes. The lambdagram is applied to the Nelson-Plosser data and the conclusions drawn from using it are compared with other analyses of this data set.
Keywords: 330